Menelaah Peluang Perkembangan Pendidikan Islam Indonesia di Masa Depan Melalui Analisis Bibliometrik - Syi'bul Huda, Ali Anhar; Syahidin, Syahidin (UIR Press, 2024)
This research, conducted in March 2024, focused on Islamic education through a Google Scholar database search, sampling 500 articles published between 2014-2024. Utilizing Publish or Perish (PoP) version 8.12 for metadata retrieval, the study analyzed publication trends, researcher productivity, and journal ranks descriptively. Results were exported into PoPCites format, mapped in Ms. Word 2021, and analyzed using VOSViewer (VV) version 1.6.20. Findings revealed fluctuating publication trends, with e-journals contributing the most (405 articles). Notable researchers include Hapza Ali (6 articles), Kemas Imron Rosadi (7 articles), and Rahmat Hidayat (4 articles). VV visualization depicted the research landscape with five clusters: Cluster 1 (6 items), Cluster 2 (6 items), Cluster 3 (4 items), Cluster 4 (2 items), and Cluster 5 (2 items), predominantly focusing on Islamic education and Islam.